2021
DOI: 10.1186/s13195-021-00794-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide epistasis analysis for Alzheimer’s disease and implications for genetic risk prediction

Abstract: Background Single-nucleotide polymorphisms (SNPs) identified by genome-wide association studies only explain part of the heritability of Alzheimer’s disease (AD). Epistasis has been considered as one of the main causes of “missing heritability” in AD. Methods We performed genome-wide epistasis screening (N = 10,389) for the clinical diagnosis of AD using three popularly adopted methods. Subsequent analyses were performed to eliminate spurious assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“… 42 , 43 The missing heritability is likely not due to simple additivity across common variants but also to contributions from rare variants as well as to non-additive effects including dominance and epistasis. 42 , 44 Studies of rare variants and Alzheimer’s disease risk have observed effects for rare coding variants in genes such as ABCA7, BIN, NOTCH3, PLCG2, SORL1, TREM and ABI3 among others 45–47 not captured by PRSs. Apart from a rare variant in TREM2 (p.Arg47His), little replication work has been reported.…”
Section: Discussionmentioning
confidence: 99%
“… 42 , 43 The missing heritability is likely not due to simple additivity across common variants but also to contributions from rare variants as well as to non-additive effects including dominance and epistasis. 42 , 44 Studies of rare variants and Alzheimer’s disease risk have observed effects for rare coding variants in genes such as ABCA7, BIN, NOTCH3, PLCG2, SORL1, TREM and ABI3 among others 45–47 not captured by PRSs. Apart from a rare variant in TREM2 (p.Arg47His), little replication work has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the predictive power of the hub genes was compared between ADNI DEGs and the recognized AD pathogenic genes [ 2 ] ( Table S12 ). APOE is the most important genetic factor of AD and accounts for approximately 5–9% of heritability [ 39 ]; thus, the prediction efficiency of hub genes was compared with recognized pathogenic genes other than APOE . ROC curves showed that the AUC of hub genes (Hub Genes AUC: 0.623) was significantly higher than that of AD pathogenic genes and AD pathogenic genes excluding APOE (Sig Genes AUC: 0.541, Sig~ APOE AUC: 0.528; DeLong’s test, p = 0.02/0.008) ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
“…Interaction effects are common in many scientific disciplines where assessing feature importance is prevalent including hydrology [31,32,33], genomics [4,34,35], and finance [36,37]. So, as was done in [7], we assess the ability of MCI and UMFI to detect non-linear interaction effects in the data.…”
Section: Non-linear Interactionsmentioning
confidence: 99%